Representações de educadores de professores sobre a formação em Letras e o ensino-aprendizagem de Língua Inglesa - Freitas, Marcela Henrique de (2018)
The present MA thesis aims at analyzing the discursive representations built by professors (educators) of English as a Second Language (ESL) in their utterances about the education process of pre-service teachers of ESL. Four specific research goals were proposed: 1) to delineate the discursive representations of the subjects about pre-service ESL teacher education and the process of teaching and learning such language 2) to analyze and interpret the interdiscursivity—the supporting axis—of these representations; 3) to confront the discursive inscription of the participating research subjects, searching for regularities and divergences in their utterance; and 4) to raise questions about how such discursivity may affect the educator’s practice, the education process and the English teaching-learning. The starting hypothesis is that professors of pre-service teachers, when uttering about the education process of their students, weave their utterances from the tension between the need to teach linguistic materiality itself (i.e., the English language and all its discursive-linguistic aspects) and the need to teach pre-service teachers to constitute themselves as ‘ESL teacher subjects’, contemplating all the social, historical, political, ideological and methodological aspects involved in such task. The thesis is theoretically based on the Applied Linguistics (AL), Pêcheux’s French Discourse Analysis (FDA), and Dialogical Discourse Analysis (DDA), drawing on Bakhtin’s conceptions of language. An analytical, descriptive, qualitative and hermeneutic methodology was applied to tackle a corpus of open testimonials provided by six professors of pre-service teachers from an undergraduate program in Modern Languages at a Brazilian federal university. The participants, who followed instructions of a script containing 23 questions related to pre-service teacher education and teaching learning of English, recorded the testimonials. The methodological tool used for corpus collection and data analysis was the proposal known as AREDA (Analysis of Discursive Resonances in Open Testimonials) created by Serrani-Infante in 1998. The analysis revealed three axis, listed as follows. Axis 1—the educator and the relation with English—was subdivided into: 1) the educator’s inscription in the discourse of endearment for English, 2) the educator’s inscription in the discourse of formal learning of English, and 3) the educator’s inscription in the discourse of legitimation of English through the contact with foreigners. Axis 2—the educator and the relation with teaching-learning of English—was subdivided into: 1) the educator’s inscription in an integration discourse, 2) the educator’s inscription in the discourse of (im)possibility of linguistic proficiency, and 3) the educator’s inscription in the criticality discourse. Finally, Axis 3—pre-service teachers’ educators and the relation with the formation process—was subdivided into: 1) the educator’s inscription in the lack of any aspect in the education process, 2) the educator’s inscription in the autonomy discourse, and 3) the educator’s inscription in the discourse of (im)possibility of education. The analysis corroborated the previously formulated hypothesis and pointed to a need of further investigating the constitutional educational process of pre-service teachers as well as new discourse-oriented studies.